IMPROVED ABILITY TO ANALYZE CASES OF HUMAN RIGHTS VIOLATIONS THROUGH INQUESTS STUDENTS OF CLASS XI IIS-1 SMA NEGERI 21 SURABAYA - Kristiwi Estuningsih (LPPM STAI Muhammadiyah Probolinggo, 2023)
There are many human rights violations in Indonesia, whether committed by the government, security forces or by the community itself. We can also easily find human rights violations around our neighborhoods that affect children, for example minors who earn money for their families or other irresponsible parties. In Law No.39 of 1999, human rights violations are every act of a person or group of people, including state officials, whether intentional or unintentional, or negligence, which unlawfully reduces, hinders, limits and revokes the human rights of a person or group of people guaranteed by this law and does not get or is feared will not get a fair and correct legal settlement. Based on the applicable legal mechanism, which is now Law No.26/2000 on Human Rights Courts, human rights violations are every act of a person or group of people, including state apparatus, whether intentionally or unintentionally or negligently, which legally reduces, obstructs, limits and or revokes the human rights of a person or group of people guaranteed by this Law, and does not get or is feared will not get a legal settlement in force. Human rights violations can be grouped into 2 types, namely gross human rights violations and minor human rights violations. Crimes of genocide and crimes against humanity are included in gross human rights violations. The crime of genocide itself, according to Law No.26/2000 on Human Rights Courts, is any act committed with the intent to destroy or annihilate all or part of a group, nation, race, ethnic group and religious group. The inquiry method is a teaching and learning activity in which students are faced with a situation/problem to then look for answers or conclusions. The answer or conclusion is not necessarily a solution to the problem or situation at hand. It can also be that the answer only reaches the level of finding things that cause the situation or problem to arise. This class action research was carried out using the Inquiry method in two cycles with the setting of Class XI IIS 1 at SMA Negeri 21 Surabaya in Semester I of the 2022/2023 academic year. This can be seen from the increase in the value of student learning outcomes before the study was: 56.11 (low), in cycle 1 there was an increase to : 67.05 and in cycle 2 is: 82.96 (good).